2021
DOI: 10.1182/blood.2021010784
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a safety switch to abrogate CD19.CAR T-cell–associated neurotoxicity

Abstract: Chimeric antigen receptor (CAR)-modified T cells targeting the CD19 antigen are approved to treat relapsed and refractory B-cell malignancies. [1][2][3][4] Despite durable objective responses, most patients experience acute toxicities such as cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS). 5 Although many cases of ICANS resolve with supportive measures, high-grade ICANS may result in status epilepticus, lasting neurologic deficits, cerebral edema, 6 and death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…iCasp9 is an apoptosis-triggering fusion protein, and rimiducid (AP1903) can induce the dimerization of iCasp9 and activate downstream caspase, eliminating the engineered CAR T-cells within 30 min [136,137]. This strategy induced dramatic and immediate CAR T-cell elimination in a 26-year-old female, effectively alleviating the ICANS symptoms and improving the ICANS grades (from 3 to 1) and the Immune Effector Cell-Associated Encephalopathy (ICE) score (from 0 to 7) within 12 h [138]. The efficacy of iCasp9 CAR T-cells in CD19 B cell malignancies is still being evaluated in clinical trials (NCT03016377 and NCT03696784).…”
Section: Elimination Switchesmentioning
confidence: 99%
“…iCasp9 is an apoptosis-triggering fusion protein, and rimiducid (AP1903) can induce the dimerization of iCasp9 and activate downstream caspase, eliminating the engineered CAR T-cells within 30 min [136,137]. This strategy induced dramatic and immediate CAR T-cell elimination in a 26-year-old female, effectively alleviating the ICANS symptoms and improving the ICANS grades (from 3 to 1) and the Immune Effector Cell-Associated Encephalopathy (ICE) score (from 0 to 7) within 12 h [138]. The efficacy of iCasp9 CAR T-cells in CD19 B cell malignancies is still being evaluated in clinical trials (NCT03016377 and NCT03696784).…”
Section: Elimination Switchesmentioning
confidence: 99%
“…Recently, Foster et al (2021) has demonstrated that acute ICANS can be effectively controlled by treating CAR-T therapy patients with the iCasp9-activating agent, rimiducidn. 23 We included an iCasp9 safety switch in our GF-CART01 design to mitigate the tumorigenicity risk associated with genetic manipulation, and we confirmed that CAR-T cells can be eliminated upon AP1903 drug treatment.…”
Section: Discussionmentioning
confidence: 60%
“…In patients who do not respond to these measures, third-line agents should be entertained, including Siltuximab ( 63 ), Anakinra ( 29 , 64 ) and high-dose Methylprednisolone (1gram daily x 3days, followed by rapid taper) ( 55 ). In products containing an inducible safety switch such as inducible caspase-9 (iC9) ( 65 ) this should be triggered in the face of serious uncontrollable toxicity. Although clinical data is lacking, preclinical models have suggested that the tyrosine kinase inhibitor Dasatinib may be utilized to transiently ablate CAR signaling by interfering with the lymphocyte-specific protein tyrosine kinase (LCK) and inhibiting phosphorylation of the CD3ζ-chain contained in the CAR ( 66 ) ( Figure 2 ).…”
Section: Principles Of Toxicity Managementmentioning
confidence: 99%